The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1191/0269215500cr345oa
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study comparing the cognitive demand of walking for transfemoral amputees using the Intelligent Prosthesis with that using conventionally damped knees

Abstract: The microprocessor-controlled prosthesis was not found to be less cognitively demanding than a conventional prosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 8 publications
(4 reference statements)
0
86
0
2
Order By: Relevance
“…The difficulty of the secondary tasks likewise varied across studies. No significant differences between the MPK and NMPK conditions were measured for users of swingonly MPKs walking on a treadmill [95], swing and stance MPK users walking in a laboratory [94], or swing and stance MPK users walking outside the laboratory over paved ground [73]. Hafner and Smith reported that subjects demonstrated a significant increase in outdoor SSWS without a significant change in divided attention task performance when using a swing and stance MPK compared with an NMPK [72].…”
Section: Cognitive Demandmentioning
confidence: 99%
See 3 more Smart Citations
“…The difficulty of the secondary tasks likewise varied across studies. No significant differences between the MPK and NMPK conditions were measured for users of swingonly MPKs walking on a treadmill [95], swing and stance MPK users walking in a laboratory [94], or swing and stance MPK users walking outside the laboratory over paved ground [73]. Hafner and Smith reported that subjects demonstrated a significant increase in outdoor SSWS without a significant change in divided attention task performance when using a swing and stance MPK compared with an NMPK [72].…”
Section: Cognitive Demandmentioning
confidence: 99%
“…Physiological measures of cognitive demand reported in the MPK literature include distance traveled during a divided attention task, SSWS during a divided attention task, sway velocity during a divided attention task, serial subtraction test, Controlled Oral Word Association Test, and the Category Test. Perceived measures of cognitive demand that have been reported include the PEQ-A and the Prosthetic Cognitive Burden Scale (PCBS) [72][73]80,[94][95].…”
Section: Cognitive Demandmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to nondisabled adults, who typically manage such conditions with ease, ambulating with a transfemoral prosthesis requires significant cognitive effort because of the loss of proprioception and motor control at the ankle and knee joints, which diminishes the normal motor and balance mechanisms relative to nondisabled individuals [13,[15][16]. The literature also describes how people with amputation must rely on visual cues in order to monitor the prosthetic device, which interferes with their ability to perform other tasks and is considered an additional cognitive burden [13,[17][18][19]. For example, persons with LLA are often required to physically look at their prosthesis when descending stairs to prevent themselves from tripping.…”
Section: Introductionmentioning
confidence: 99%